(untitled) (Experimental biology, 2023)
An increase in anthropogenic activity is the main factor causing changes in the climate, atmosphere, biosphere and cryosphere of the Earth, which directly or indirectly affect ecosystems at the local, regional and global levels. Before the industrial revolution, the pollution factor was associated with natural causes, but with the onset of the industrial revolution in the 19th century, our ecosystem began to be polluted many times more. An increase in pollution leads to such consequences as drought, an increase in the desert, global warming, melting glaciers, etc.